A comparative assessment of safety and tolerability of metoprolol versus carvedilol in patients of chronic stable angina - Bansal, Megha; Gari, Manju; Varshney, Manisha (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Angina pectoris is a clinical manifestation characterized by chest pain typically in substerum radiating to left arm, jaw, back lasting for 1-5 minutes and is relieved by rest. Beta blockers are one of the drugs indicated in angina. The aim of the study is to compare safety and tolerability of metoprolol and carvedilol in patients of chronic stable angina. Methods: The study done is randomized, open label, parallel type where tablet carvedilol and tab metoprolol is given in a group of 50 patients each. The patients were followed thereafter on 8th, 16th, 24th week to study safety in terms of haematological parameters like complete blood count, liver function tests, renal function tests, serum sodium, serum potassium, fasting blood glucose, 2 hours post prandial blood glucose, HbA1C, and Lipid profile and tolerability in terms of side effects. The study was conducted for one year and the data was assessed by relevant statistical analysis where p value <0.05 was considered significant. Results: It was seen that the disease was most common in the age group of 51-60 years with male preponderance, and carvedilol was found to cause non-significant decrease in Serum Triglyceride with no change in total cholesterol, HDL-C, LDL-C was found. No significant changes were observed in metoprolol group. There was no significant difference observed when blood sugar profile and other haematological parameters were considered. Both drugs were considered to be equally tolerable. Conclusions: Compared with carvedilol and metoprolol in patients of chronic stable angina, carvedilol resulted in better lipid profile whereas metoprolol showed no changes in lipid parameters.